2021
DOI: 10.3390/ijerph18168502
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-Perception Equal the Truth When Judging Own Body Weight and Height?

Abstract: Background: Data from the research project “Fitness clubs—a venue for public health?” provided an opportunity to evaluate the accuracy of self-reported body weight and height, and subsequent Body Mass Index (BMI), as well as the “trueness” of novice exercisers perception of weight status category, which has not been examined in this population. The aims were to examine self-reported body weight, height, and calculated BMI data from an online survey compared with measured data at fitness club start-up, investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Crucial is to consider relation of two basic factors of physical development that is height and body mass. On the one hand, we can observe the acceleration of human development, which manifests itself in a greater body height of successive generations, but on the other, we see dangerous for health development of overweightness and obesity [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Crucial is to consider relation of two basic factors of physical development that is height and body mass. On the one hand, we can observe the acceleration of human development, which manifests itself in a greater body height of successive generations, but on the other, we see dangerous for health development of overweightness and obesity [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, self-report of body weight and height may be biased by the individual's feelings at the time they fill out the questionnaire and participants often want to present the best versions, or at least a socially acceptable version of themselves ( 60 ). Yet, we have previously published a paper showing that both male and female fitness club members reported body weight and height reasonably accurately and that BMI based on self-report appears to be a valid measure ( 61 ). Further, we believe that using a questionnaire to gather data on BMI was an appropriate measurement method during the COVID-19 pandemic and social lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the BMI was calculated using height and weight from self-reported questionnaires in the main study. Previous studies have shown no substantial differences between BMI calculated from self-reported height and weight and that calculated from measured height and weight, indicating that self-reported weight and height are useful (69). Therefore, it is unlikely that the use of self-reported height and weight data significantly distorted the results.…”
Section: Limitationsmentioning
confidence: 94%